POLA KOMUNIKASI KOMUNITAS DRIVER GOJEK TANGKERANG SELATAN (GTS) PEKANBARU DALAM MENJAGA SOLIDARITAS KELOMPOK - Muhammad Habibi Fahmi; Hevi Susanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Pekanbaru South Tangkerang Gojek Driver Community (GTS) is one of the first Gojek Driver communities in Pekanbaru, not only being the first community, this community is also the main target of the Pekanbaru Police Chief. As well as getting a special program directly from PT. Gojek Indonesia is domiciled in Pekanbaru, namely the Healthy Gojek Pekanbaru Program. GTS is also active in social activities and also holds regular Community meetings every month. Some of these aspects made researchers interested in examining how communication patterns exist in the Pekanbaru Gojek Driver Community in South Tangerang (GTS) in maintaining group solidarity. This study uses a qualitative descriptive research method. The research subjects here are the Heads and Members of the South Tangerang Gojek Driver Community (GTS) Pekanbaru using purposive sampling and accidental sampling techniques. This study uses data collection techniques through interviews, observation and documentation. To achieve the validity of the data in this study the authors used the source triangulation technique. The results of this study indicate that the pattern of communication that exists in Gojek Tangkerang Selatan is multidirectional communication (all channels), where interaction in this community involves more than two people who exchange ideas dialogically. The Communication Pattern Network of the South Tangerang Gojek Driver Community (GTS) Pekanbaru in Maintaining Solidarity is in accordance with all communication networks.